Emotional Labour in Magazine Work: Suppressing and evoking emotions as part of project-based teamwork. (16th March 2018) - Soronen, Anne
Abstract : This ethnographic research concerns the management of emotions in the editorial offices of the Finnish fashion-oriented lifestyle magazines, Elle Finland and Trendi . The material was collected through focused interviews and participant observation in editorial shoots. The analysis focuses on the informants' ways of acting in the editorial shoots and their experiences in their work and the role of emotions in content production and co-operative work practices. The study demonstrates that emotional labour is required in production of content that is aimed to move, please or surprise the model reader and through her, the actual readers of the magazine. The members of the photography team are inclined to suppress feelings of anxiety and at the same time support and encourage other team members and the photographed subject. Emotional labour maintains stability in a tightly scheduled and goal-oriented teamwork, and enables team members to attune to the intimate and convivial atmosphere. The study also gives evidence about cruel optimism as it points out how magazine staff adjust to the uncertainty of the magazine field and the increased personal workload by invoking in themselves feelings of enjoyment and suppressing feelings of strain.